Nilai-nilai Akhlakul Karimah dalam Film Ustadz Milenial - Muthia Azizah; Rini Rahman (FONDATIA, 2022)
This research is motivated by the number of films that are less educative, especially in conveying religious understanding, which tend to be less educative films, this millennial ustadz film explains that the important point to be conveyed is religious knowledge, one of which is moral values. The purpose of this study was to determine the moral values contained in the millennial ustadz film in episodes 1-5. This study uses a type of library research or literature study with a qualitative method approach, the data source is the millennial ustadz film episode 1-5. From the results of the research, morality is divided into three parts, namely, first, morality to Allah SWT, such as: gratitude, trustworthiness, being kind and remembering Allah SWT. , while to the family, such as: obedient to parents and fellow human beings and the three morals to the environment and society such as happy to help.